A Direct Test of the Theory of Comparative Advantage: The Case of Japan - Bernhofen, Daniel M.; Brown, John C. (Journal of Political Economy, 2004)
We exploit Japan’s sudden and complete opening up to international trade in the 1860s to test the empirical validity of one of the oldest and most fundamental propositions in economics: the theory of comparative advantage. Historical evidence supports the assertion that the characteristics of the Japanese economy at the time were compatible with the key assumptions of the neoclassical trade model. Using detailed product‐specific data on autarky prices and trade flows, we find that the autarky price value of Japan’s trade is negative for each year of the period 1868–75. This confirms the prediction of the theory.